Tingkat Bunga, Inflasi, dan Investasi: Hubungan dan Dampaknya dalam Perekonomian - Bona Vintura Suyana Pandiangan; Gresia Apriyani; Siti Sarah Tumangger; Sri Ramadhani Siregar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines the relationship between interest rates, inflation, and investment, as well as their impact on economic growth. High interest rates tend to hinder investment by increasing capital costs, while uncontrolled inflation can create economic uncertainty that negatively affects investment decisions. Based on the Fisher Effect concept, the nominal interest rate is the sum of the real interest rate and the expected inflation rate, indicating that changes in inflation directly influence central bank interest rate policies. An analysis of various journals reveals that interest rates have a negative relationship with investment, while inflation can have both positive and negative effects depending on its level. If inflation remains stable, investment tends to increase; however, if inflation is too high, purchasing power declines, and investors seek safer assets. On a macroeconomic scale, healthy investment is a key factor in driving economic growth, as it contributes to job creation and increased production. Therefore, a balanced monetary policy is essential to maintaining inflation stability, interest rates, and investment growth to ensure sustainable economic development.